Effect of Shelter-in-Place Orders and the COVID-19 Pandemic on Orthopaedic Trauma at a Community Level II Trauma Center. Issue 9 (September 2020) - Stoker, Steven; McDaniel, Dalton; Crean, Trevor; Maddox, Joshua; Jawanda, Gurkirat; Krentz, Neal; Best, Jacob; Speicher, Mark; Siwiec, Ryan
Abstract : Objectives: To evaluate the effect of the COVID-19 pandemic and the "shelter-in-place" order on orthopaedic trauma presenting to a community level II trauma center. It is hypothesized that the overall number of orthopaedic trauma encounters (OTEs), the number of OTEs related to both high and low severity injuries, and the proportion of OTEs related to high severity versus low severity injuries decreased compared with previous years. Methods: A retrospective analysis was conducted of OTEs between 2016 and 2020. High and low severity OTEs were classified according to an algorithm created by the researchers. Data were statistically analyzed and compared with external data for traffic counts, motor vehicle accidents, and Transportation Security Administration checkpoints. Results: A 45.1% decrease ( P = 0.0005) was seen in OTEs from March and April 2016–2019 compared with 2020. The decrease began approximately 12 days before the shelter-in-place order. There was a 58.8% decrease in high severity injuries with a fracture ( P = 0.013) and a 42.9% decrease in low severities injuries ( P = 0.0003). The proportion of high to low severity OTEs was unchanged. Conclusions: The quantity of OTEs was significantly affected by the COVID-19 pandemic and Michigan shelter-in-place order. A decrease in both high and low severity OTEs was found; however, there was no statistically significant change in the ratio of high to low severity OTEs compared with previous years. Although it is difficult to determine what portion of the decrease in OTE is attributable to the shelter-in-place order versus the COVID-19 pandemic in general, data suggest both play a role. Level of Evidence: Therapeutic Level III. See Instructions for Authors for a complete description of Levels of Evidence. Abstract : Supplemental Digital Content is Available in the Text.